Efektivitas Program Pembinaan Kerohanian di Rumah Tahanan Negara Kelas IIB Painan Kabupaten Pesisir Selatan - Reisya Yuarilda; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
Although the effectiveness of spiritual development programs for inmates has been examined in various studies, research specifically addressing their implementation in state detention centers with dual functions and overcrowded conditions remains limited. This study aims to analyze the effectiveness of the Spiritual Development Program at the Painan Class IIB State Detention Center, Pesisir Selatan Regency, and identify the factors influencing its implementation. The study employed a qualitative approach with a descriptive design. Informants were selected through purposive sampling and comprised the Head of the Detainee Services Subsection, a religious instructor from the Ministry of Religious Affairs, and inmates who actively participated in the program. Data were collected through in-depth interviews, observations, and document analysis and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the spiritual development program has generally been implemented effectively based on five indicators: program understanding, target appropriateness, timeliness, goal attainment, and tangible change. However, its implementation has not yet been supported by a formally structured system of documentation, monitoring, and evaluation. Based on Steers’ organizational effectiveness framework, the program’s supporting factors include the availability of prayer-room facilities and formal collaboration with the Ministry of Religious Affairs, whereas the inhibiting factors include the detention center’s dual functions, overcrowded conditions, and limited staffing. This study concludes that the Spiritual Development Program at the Painan Class IIB State Detention Center has fulfilled the effectiveness indicators but requires a strengthened monitoring and evaluation system to ensure more structured and sustainable implementation. These findings contribute to the development of research on program effectiveness in the correctional context and provide practical implications for strengthening the governance of spiritual development programs in state detention centers that perform dual functions.